Hearing loss, coloboma and left ventricular enlargement in a boy with an interstitial 10q26 deletion. Issue 2 (29th April 2016) - Ramos, Maria; Wilkens, Alisha; Krantz, Ian D.; Wu, Yaning
Abstract : Distal deletion of the long arm of chromosome 10 with breakpoints mapped at 10q26 is a well‐recognized contiguous genomic disorder. A wide spectrum of clinical findings is seen in affected individuals and the common clinical features include craniofacial dysmorphia, developmental delay, intellectual disability, hypotonia, cardiovascular defects, and urogenital malformations. We report herein on a male patient with a 5.5 Mb interstitial deletion of 10q26.11q2613 and compare his clinical presentation to previously reported cases. Apart from characteristic phenotypes seen in 10q26 deletion syndrome, he presents with colobomas and left ventricle enlargement. These are cardiovascular and ophthalmological findings that have not been described in prior cases. © 2016 Wiley Periodicals, Inc.